2015
DOI: 10.1155/2015/540247
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative PDT Experiment of the Inactivation of HL60 on Modified TiO2 Nanoparticles

Abstract: Four samples of modified titanium dioxide (TiO2), Fe/TiO2(2 wt%), Fe/TiO2(5 wt%), and 5-ALA/TiO2, were experimented in photodynamic therapy (PDT) on leukemia cells HL60, performing promising photocatalytic inactivation effect. Fe/TiO2and 5-ALA/TiO2were synthesized in methods of precipitation and ultrasonic methods, respectively. X-ray diffraction spectra and UV-Vis spectra were studied for the samples’ crystalline phase and redshift of absorption peak. Further, FTIR spectra and Raman spectra were obtained to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…These results showed that with an increase in the UV exposure time, the cell viability decreased. The results of this research are in good agreement with the previous published data ( Lu et al, 2015 ). Toxicity occurs because there is an excess of low density lipoprotein (LPL) receptors in liver cancer tissue, which attracts more antioxidant agents occupied by TEMPO-treated TiO 2 NRs.…”
Section: Resultssupporting
confidence: 93%
“…These results showed that with an increase in the UV exposure time, the cell viability decreased. The results of this research are in good agreement with the previous published data ( Lu et al, 2015 ). Toxicity occurs because there is an excess of low density lipoprotein (LPL) receptors in liver cancer tissue, which attracts more antioxidant agents occupied by TEMPO-treated TiO 2 NRs.…”
Section: Resultssupporting
confidence: 93%
“…As reported in our previous work, coupling TiO 2 with low band gap energy metal or nonmetal to form a heterostructure is a feasible strategy to extend the visible light response range of TiO 2 -based nanocomposites and thus improve the photocatalytic performance [13][14][15][16]. CdS, CdSe, and CdTe belong to the II-VI group cadmium-based quantum dot material [17,18].…”
Section: Introductionmentioning
confidence: 92%